Psychological coaching as a driver of young entrepreneurs’ enhanced networking capabilities - Ana Galvão; Marco Pinheiro (Tourism & Management Studies)
According to the Global Entrepreneurship Index 2018, Portugal’s entrepreneurship is suboptimal due to Portuguese entrepreneurs’ low networking capacity. This research focused on psychological and personality traits that may contribute to this suboptimal performance. The study was based on 331 young adults who answered a questionnaire composed of three parts: sociodemographic questions, the Portuguese Entrepreneurial Psychological Traits Inventory (PEPTI) and the Big Five Inventory (BFI44). The results show that young Portuguese entrepreneurs score higher on the PEPTI and four of the BFI-44’s five dimensions. However, the differences detected in the agreeableness trait scores are not statistically significant, which is a possible reason for the reported suboptimal networking skills. Since networking capabilities are important for successful entrepreneurship, the findings include the need to create a psychological coaching programme for young Portuguese entrepreneurs to enhance various soft skills that could improve their networking capabilities.